Effect of Physalis peruviana "tomatillo" fruit extract in Mus musculus var. swis with induced hyperlipidemi. - Campos Florián, Julio (2011)
The objective of this research was to determine the hypolipidemic activity of the fruit of Physalis peruviana "tomatillo" in a model of acute hyperlipidemia induced by triton. Mus musculus var. swis males as experimental animals. We worked with four groups of mice, the white group received distilled water orally and saline intraperitoneally, the control group received distilled water orally and intraperitoneally triton, the problem group 1 received orally 0.05g/100g Physalis peruviana extract intraperitoneally and triton and the problem group 2 received orally 0.2g/100g extract of Physalis peruviana and triton intraperitoneally. After 24 hours of administering the treatments were performed measurements of serum cholesterol and triglycerides. Mean levels of cholesterol (mg/dL) were: 58.87 ± 11.54 (white), 121.71 ± 15.00 (control), 58.08 ± 9.21 (Problem 1) and 66 78 ± 16.77 (Problem 2). Average levels of triglycerides (g /L) were: 0.48 ± 0.07 (white), 1.84 ± 0.18 (control), 0.34 ± 0.10 (Problem 1) and 0.94 ± 0.25 (Problem 2). We found significant reductions (p <0.000) concentrations of both cholesterol and triglycerides in relation to those obtained in the group treated only with Triton.